Understanding pro-environmental consumption behaviour change : the case of haze in Singapore and the Indonesian forest fires - Zenata, Putera (2013)
Cases of haze in Singapore have been a yearly occurrence for more than a decade and are rued by the local population. The haze is a product of the forest fires across Borneo and Sumatra in Indonesia where the slash and burn techniques are used by small farmers and multinational corporations alike to clear lands for plantations, most commonly palm oil. Regulating people’s consumption behaviour is arguably the most sustainable way to prevent forest fires, and hence avoiding future cases of haze. However, despite having the highest per capita consumption of palm oil in the region, the Singapore population has directed much of the blame for haze towards the ineptitude of the Indonesian government in overcoming the forest fires. The study seeks to find out if the people in Singapore understand how consumption of palm oil indirectly causes the haze and examines the extent of people’s willingness to change their palm oil consumption behaviour. Factors such as environmental values, attitudes and giving a verbal pledge are found to significantly affect participant’s propensity to change their consumption behaviour. On the other hand, the reported degree of disruption the haze cases have inflicted on the participants’ daily life turns out to be mostly irrelevant in predicting their consumption behaviour change. The priming experiment conducted on real time shoppers finds that cue-cards advocating haze free Singapore is less successful in reducing their palm oil product purchases in the super market when compared to cue cards advocating orang-utan preservation.